The Effect of Wordwall Based Media on Students' Procedure Text Achievement in Ninth Grade Students - Adnyana, I Nyoman Gede Wisnu; Dewi, Kadek Sintya (Universitas Pendidikan Ganesha, 2022)
The goal of this study was to analyse if there was a difference in student achievement in class IX when utilizing the Wordwall application to write procedure texts. Post-test In this study, only the Control Group Design was used. The students in this study were grade IX. One complete group cluster random sampling was utilized to collect the sample. There were two sample groups in this study: an experimental group that was taught using the Wordwall application, and a control group that was taught using the traditional technique or without the use of the Wordwall program. A post-test was used to collect data after the two groups received different treatments for seven meetings. The data was then analyzed using descriptive statistical analysis and inferential analysis. The experimental group scored better in writing, with a mean score of 77.20 compared to 73.70 for the control group, according to descriptive statistical analysis. Furthermore, based on hypothesis testing in inferential analysis, the computed t value = 2.112 (tobs) is greater than the t table value of 2.001 (tcv) with a standard alpha level (a = 0.05). As a result, the first hypothesis is rejected in favour of the alternate hypothesis. As a result, it can be determined that there is a significant difference in the learning accomplishment of class IX students when it comes to creating procedural texts utilizing the Wordwall application.